Penggambaran Kembang Tujuh Rupa dalam Seni Lukis Berbahan Dasar Natural Pigment - Rohandi, Teten; Kusdiana, Hilman Cahya; Noor Zaman, Farid Kurniawan (Jurusan Seni Rupa ISBI Bandung, 2024)
Flowers have been part of Indonesian tradition since ancient times. The tradition of using flowers as symbolization and funeral or traditional rituals in Indonesia is used in various regions of Indonesia, including in West Java, such as tingkeban, death ceremonies, nyekar, circumcision, grave pilgrimages, folk entertainment, and so on. In the field of modern art, flowers are used as objects in painting. In addition, school, studio and college curricula mostly use Western curricula with modern content, media and techniques. This research was carried out to create works of painting, especially on paper and glass media using natural dyes. The focus of the theme raised is the tradition of the 7 types of flowers in Sundanese culture in general. In this research, qualitative research methods were used. The creation steps can be divided into three main stages, namely; the first stage, in the form of searching for ideas or ideas; the second stage, in the form of deepening or maturation of the idea or ideas; The third stage, namely the final stage, is the realization of the work of art. It is hoped that the results of this research can add to the repertoire of Indonesian fine arts in terms of media, as well as provide an understanding to the wider audience regarding the 7 types flower tradition in West Java.